2019
DOI: 10.1111/ans.15471
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and gastric acid‐suppression medication 20 years after laparoscopic fundoplication

Abstract: Background Laparoscopic fundoplication is an effective treatment for gastro‐oesophageal reflux disease (GERD). We aimed to assess quality of life (QoL), long‐term residual symptoms, patient satisfaction and use of acid‐suppression medication at 5, 10 and 20 years after surgery. Methods We identified a cohort of 100 patients who underwent laparoscopic fundoplication between 1993 and 1998. The validated QoL questionnaires Short Form health survey (SF‐36), and Quality‐of‐Life in Reflux and Dyspepsia (QOLRAD), as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 32 publications
(123 reference statements)
0
19
0
1
Order By: Relevance
“…[20,21] Campenello et al (2019) found that 84% of patients would recommend the procedure with data collected 20 years postoperatively. [22] A component of LF that is difficult to conceptualize is how patient selection affects outcomes. Although we were not able to fully develop a framework for how patient selection influenced outcomes across our review, a stringent patient selection process was highlighted by Hwang (2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20,21] Campenello et al (2019) found that 84% of patients would recommend the procedure with data collected 20 years postoperatively. [22] A component of LF that is difficult to conceptualize is how patient selection affects outcomes. Although we were not able to fully develop a framework for how patient selection influenced outcomes across our review, a stringent patient selection process was highlighted by Hwang (2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Dassinger et al (2004) reported that 12% of patients experienced post-operative reflux. [ 20 ] Long-term studies in tertiary centers such as Robinson et al (2014) and Campanello et al (2019) found rates of post-operative reflux of 19.6% and 26% respectively with patients followed-up for up to 20 years following LF [ 21 , 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…In addition to questionnaires on general QOL, disease-specific instruments are used to measure those areas of QOL that are specific to a particular disease. The longest follow-up series for QOL after CLF are currently limited to 20 years [16,19,32,33]. Moreover, there is a lack of comparable long-term follow-up data in the literature regarding RALF.…”
Section: Discussionmentioning
confidence: 99%
“…1). In the very heterogeneous literature, a mean long-term follow-up of at least 10 years [15][16][17][18][19] and moreover is reported and defined for the assessment of quality of life in GERD, so it seemed reasonable and feasible to us, and we decided on a 12-year follow-up for organizational reasons. Patients were sent a standardized questionnaire and were offered a follow-up visit at the outpatient clinic or an assessment via telephone call.…”
Section: Methodsmentioning
confidence: 99%
“…60 % der Patienten, 24 % der Patienten haben immer noch Schwierigkeiten mit Ruktation, die Dysphagierate ist hingegen mit 3-6 % sehr nieder. Dabei sind 87 % der operierten Patienten auch nach 20 Jahren mit dem Ergebnis zufrieden und 84 % der Patienten würden den Eingriff weiterempfehlen [37].…”
Section: Lebensqualität Nach Fundoplicatiounclassified